El hombre que embotelló el sol : la leyenda del Benidorm turístico - Bernàcer, Óscar, 1978-; Martínez, Joana (Martínez Ortueta) (Nakamura Films, 2016)
The amazing story of how Benidorm became a major tourist resort thanks to Pedro Zaragoza, the legendary mayor with a Vespa. This unique man was able to create a modern city out of nothing, turn it into a leisure playground for the middle class, and then pitch it from London to Lapland with marketing strategies that still seem incredible even today. Did it all really happen?--